Eksplorasi Kecerdasan Spiritual dalam Kehidupan Rohani Jemaat: Perspektif Kasih Allah dalam Efesus 3:18-19 - Purwonugroho, Daniel Pesah (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2024)
Spiritual intelligence is the intelligence required by every believer. Spiritual intelligence is rooted in the spiritual reality within the life of the congregation. Spiritual intelligence in the spiritual life of the congregation can be explored when the congregation realizes the great and miraculous love of God. Ephesians 3:18-19 provides a description of the great and noble dimensions of God's love. God's love serves as the foundation for the congregation to build their spiritual life upon. As the congregation develops a true understanding of God's love according to Ephesians 3:18-19, exploration of spiritual intelligence within the spiritual life of the congregation can occur, resulting in an enhancement of the congregation's spiritual life. Through a descriptive qualitative approach, it can be concluded that spiritual intelligence in the spiritual life of the congregation can be explored to experience enhancement with the foundation of understanding God's love in Ephesians 3:18-19. Understanding God's love in Ephesians 3:18-19 can lead the congregation to explore spiritual intelligence in the spiritual life of the congregation.AbstrakArtikel ini dibuat untuk mengeksplorasi kecerdasan spiritual dalam kehidupan jemaat dalam perspektif kasih Allah di Efesus 3:18-19. Kecerdasan spiritual adalah kecerdasan yang dibutuhkan setiap orang percaya. Kecerdasan spiritual didasarkan kepada realitas rohani di dalam kehidupan jemaat. Kecerdasan spiritual dalam kehidupan rohani jemaat dapat dieksplorasi saat jemaat menyadari tentang kasih Allah yang besar dan ajaib. Efesus 3:18-19 memberikan sebuah deskripsi dimensi kasih Allah yang agung dan mulia. Kasih Allah menjadi dasar bagi jemaat untuk membangun kehidupan rohani. Saat jemaat membangun pemahaman yang benar akan kasih Allah sesuai dengan Efesus 3:18-19, eskplorasi kecerdasan spiritual jemaat dapat terjadi sehingga mengalami peningkatan di dalam kehidupan rohani jemaat. Dengan menggunakan pendekatan kualitatif deskriptif, dapat disimpulkan bahwa kecerdasan spiritual dalam kehidupan rohani jemaat dapat dieksplorasi untuk mengalami peningkatan dengan fondasi pemahaman kasih Allah dalam Efesus 3:18-19. Pemahaman kasih Allah dalam Efesus 3:18-19 dapat membawa jemaat mengeksplorasi kecerdasan spiritual dalam kehidupan rohani jemaat.